Three hawkweeds (Hieracium, Asteraceae) from the Netherlands typified and raised to species rank. (28th January 2013) - Haveman, Rense
<x xml:space="preserve">Abstract</x> After a short sketch of Dutch hieraciology, three taxa belonging to Hieracium sectt. Vulgata and Tridentata that were described from the Netherlands at the rank of subspecies or variety by Zahn are typified and raised to species rank. Hieracium meppelense (Zahn) Haveman comb. et stat nov. is found in the province of Drenthe in the northeastern part of the country, H. limburgense (Zahn) Haveman comb. et stat nov. in south‐Limburg in the southernmost part and H. macrodontophyllum (Van Soest et Zahn) Haveman comb. et stat nov. in the surroundings of Nijmegen and Arnhem, and further north in the central sand area. Photographs of the types as well as maps with the hitherto known distribution of these three species are included.